Information underpinning anticipation of goal-directed throwing - Bourne, M.; Bennett, S. J.; Hayes, S. J.; Smeeton, N. J.; Williams, A. M. (Attention, Perception, & Psychophysics, 2013)
We identified the information used to anticipate throw direction in handball. In two experiments, we examined how anticipation performance is affected when the information from one of five body areas (right arm, shoulders, hips, trunk, or total throw side) was either neutralized or decoupled from the motion of other body segments. In the first experiment, performance was significantly reduced when information from the throwing arm was neutralized, irrespective of skill levels. Skilled participants were negatively affected when the shoulders, hips, and trunk were neutralized, whereas less-skilled participants showed trends toward improvement under identical conditions. In the second experiment, partially disrupting relative motion via decoupling was not enough to reduce the anticipation performance among skilled participants to chance levels, whereas less-skilled participants lost their ability to anticipate in three conditions. Our findings suggest that skilled and less-skilled participants employ different information extraction strategies, yet information from the throwing arm is critical to anticipation for both groups. The two experiments suggest that relative motion mediated by both the absolute displacement trajectories of individual marker locations and their relative timings are important in informing anticipation, irrespective of skill level.